Hypertension and its association with anthropometric indexes among pre-university students - Cheah, W.L; Helmy, Hazmi; Chia, Hui Qi; Empiang, Tindin; Nur Adilah, Ahmad Zafri; Syarul Haziq, Mohd Shah (de Gruyter, 2015)
Abstract: Hypertension has become increasingly common among adolescents. This study aimed to investigate the prevalence of hypertension and its association with anthropometric indexes among pre-university students. This was a cross-sectional study carried out among pre-university students of a public university. Anthropometric measurements were conducted using mobile stadiometers, digital body fat scales and measuring tapes. Body fat percentage was measured with a body composition analyzer, and blood pressure was determined using digital blood pressure monitors. Statistical analyses were done using Statistical Package for Social Sciences (SPSS) Statistics 20. A total of 218 respondents participated in the study. The prevalence of hypertension at risk was 7.3%, which was higher among males (16.7%). About 22% of the respondents were overweight and obese. The majority of males had a normal waist circumference (WC) (75.9%), but almost half of females had a WC value in the unhealthy category (47.0%). Females had higher conicity indexes and body fat compared to males. Respondents who were found to have hypertension at risk had a higher prevalence of being overweight and having unhealthy WC and waist-to-height ratio and had high conicity indexes and a high percentage of fat. Risk factors independently associated with hypertension at risk included male gender (odds ratio = 4.213, 95% CI, 1.238–14.342) and body mass index (odds ratio = 7.865, 95% CI, 1.165–53.099). Regular screening of hypertension at risk among adolescents and initiation of early treatment for those affected should be conducted to avoid further complication in later life.